138k views
4 votes
Compute each product, and combine like terms (√x+2)(√x-2).

User Coda
by
6.2k points

1 Answer

2 votes

Answer:

x-4

Explanation:

We have to calculate each product and combine like terms in the following

(√x+2)(√x-2)

Now, (√x+2)(√x-2) {We have to apply the formula (a+b)(c+d) = a(c+d)+b(c+d)}

= √x(√x-2) + 2(√x-2)

= √x.√x -2√x +2√x-2.2

= x-2√x+2√x -4 {Since, √x.√x =x , using the formula xᵃ. xᵇ =x⁽ᵃ⁺ᵇ⁾ }

Now, combining the rational and irrational terms separately we get,

=(x-4)+(2√x-2√x)

=x-4 {Since 2√x and -2√x cancel each other}

(Answer)

User Vak
by
5.2k points